CEACAM expression in an in-vitro prostatitis model - Kube-Golovin, Irina; Lyndin, Mykola; Wiesehöfer, Marc; Wennemuth, Gunther (Frontiers in Immunology, 2023)
Prostatitis is an inflammatory disease of the prostate gland, which affects 2-16% of men worldwide and thought to be a cause for prostate cancer (PCa) development. Carcinoembryogenic antigen-related cell adhesion molecules (CEACAMs) are deregulated in inflammation and in PCa. The role of CEACAMs in prostate inflammation and their possible contribution to the malignant transformation of prostate epithelial cells is still elusive. In this study, we investigated the expression of CEACAMs in an in-vitro prostatitis model and their potential role in malignant transformation of prostate epithelial cells.Normal prostate epithelial RWPE-1 cells were treated with pro-inflammatory cytokines to achieve an inflammatory state of the cells. The expression of CEACAMs and their related isoforms were analyzed. Additionally, the expression levels of selected CEACAMs were correlated with the expression of malignancy markers and the migratory properties of the cells.This study demonstrates that the pro-inflammatory cytokines, tumor necrosis factor alpha (TNFα) and interferon-gamma (IFNγ), induce synergistically an up-regulation of CEACAM1 expression in RWPE-1 cells, specifically favoring the CEACAM1-L isoform. Furthermore, overexpressed CEACAM1-L is associated with the deregulated expression of JAK/STAT, NFκB, and epithelial-mesenchymal transition (EMT) genes, as well as an increased cell migration.We postulate that CEACAM1 isoform CEACAM1-4L may synergistically contribute to inflammationinduced oncogenesis in the prostate.